2006
DOI: 10.4067/s0034-98872006000800004
|View full text |Cite
|
Sign up to set email alerts
|

Identificación de mutaciones en el gen CYBB que llevan al fenotipo de la enfermedad granulomatosa crónica ligada al cromosoma X: Reporte de una nueva mutación

Abstract: Background: The X-linked form of chronic granulomatous disease (CGD) is a primary immunodeficiency that affects phagocytes of the innate immune system and is (Rev Méd Chile 2006; 134: 965-72).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
1
1
0
2
Order By: Relevance
“…Thus, Pulvirenti et al [13] revealed that children with CGD showed greater difficulties in the social and school area, having more difficulty relating to peers and behavioral and emotional problems. Findings that are in line with the study by Varni et al [14,18], which reveals that in general psychosocial health and emotional functioning in children with chronic pathologies, as well as in their parents, is lower compared to healthy children, affecting the HRQoL of these children, patients and their parents. Cole et al [15,18] evaluated the quality of life of children with CGD who received a hematopoietic stem cell transplant (HSCT) and revealed that their HRQoL is good after HSCT, resulting in better emotional, social and school functioning.…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…Thus, Pulvirenti et al [13] revealed that children with CGD showed greater difficulties in the social and school area, having more difficulty relating to peers and behavioral and emotional problems. Findings that are in line with the study by Varni et al [14,18], which reveals that in general psychosocial health and emotional functioning in children with chronic pathologies, as well as in their parents, is lower compared to healthy children, affecting the HRQoL of these children, patients and their parents. Cole et al [15,18] evaluated the quality of life of children with CGD who received a hematopoietic stem cell transplant (HSCT) and revealed that their HRQoL is good after HSCT, resulting in better emotional, social and school functioning.…”
Section: Introductionsupporting
confidence: 91%
“…The presence of bacterial and fungal infections and granulomas are mainly characteristic of EGC [18], with the response to viral infections being normal. Bacterial infections are usually symptomatic, accompanied by fever and leukocytosis; while fungal infections present with less fever and less leukocytosis.…”
Section: Diagnosticmentioning
confidence: 99%
“…De las cinco proteínas que forman el de las EGC, y origina la forma ligada a X. Los defectos en los NCF1, NCF4 y NCF2, respectivamente, producen las formas autosómicas recesivas 3,7 .…”
Section: Discussionunclassified
“…La terapia génica con vectores retrovirales y lentiviral puede reconstituir la actividad de la NADPH oxidasa en las promedio de supervivencia de 40 años. En general, las tasas - [2][3][4][5] . con afectación pulmonar, ganglionar, ósea y de piel, y formación de granulomas.…”
Section: Discussionunclassified